Prevalence of and Factors Associated with Undernutrition in Southern Bangladesh: A Cross-Sectional Study - Haque, Md. Uzzal; Hasan, Md. Tarek; Rahman, A.M. Shihabur; Hasan, Md. Mohibul; Islam, Shahriar; Chouduri, Aktar Uzzaman (International Journal of Child Health and Nutrition, 2023)
Background: Undernutrition is one of the main causes of child mortality and morbidity in Bangladesh. This study aimed to assess the prevalence and determinants of undernutrition among children aged six to fifty-nine months in the Jashore and Khulna districts of southern Bangladesh. Methods: The random sampling technique was used to select 400 children of 6–59 months of age. Data were collected through face-to-face interviews using a structured questionnaire and anthropometric measurements. The weight and height of children were taken using a digital weighing scale, measuring tape, and stadiometer following standard protocols. Children’s undernutrition was estimated by stunting, wasting, and being underweight. The logistic regression analyses were done to assess the factors associated with undernutrition. Results: The prevalence of stunting was 57% (95% CI: 52.1–61.8) which was positively associated with diarrhea, illiterate mothers, absence of sanitary latrine, and no antenatal care (ANC). The wasting prevalence was 13% (95% CI: 10.1–16.7) which remained directly associated with family size (≥6 members), low household income, and family planning methods. The rate of prevalence of underweight was 27.8% (95% CI: 23.6–32.3) which was significantly associated with illiterate mothers, low household income, family size (≥6 members), lack of pure drinking water, and complementary feeding started before six months. Stunting was more prevalent (74.7%) in the age group of 42–53 months compared to other groups, and boys (60.7%) were more stunted than their counterparts (52.9%). Conclusions: The magnitude of childhood undernutrition was high among the studied participants. Nutritional interventions should be implemented on the basis of significant factors in the local context to tackle this problem in Bangladesh effectively.